THE REGULATION OF DISCLOSURE PRINCIPLE IN EQUITY CROWDFUNDING (A COMPARISON BETWEEN INDONESIA AND UNITED STATES OF AMERICA) - Syarifah Zahra Al Haddar; Inda Rahadiyan (Mimbar Hukum, 2021)
Abstract Technological developments greatly make it easy for users, including in matters of financial technology (FinTech), which has also led to the innovation of Equity Crowdfunding (ECF). ECF is a new financing method seeking funding for Small Medium Enterprises (SMEs/UMKM) business development. In some developed countries such as the United States of America (US), the ECF has a systematic regulation of the disclosure principle. These rules are intended to protect the process of organising the ECF legally and professionally. In Indonesia, the ECF has just developed and has undergone two regulatory changes, from Financial Services Authority Regulations (POJK) No. 37 2018 to POJK No. 57 of 2020. The regulation of the disclosure principle in Indonesia is still not clear enough compared to the US based on Title III The Jumpstart Our Business Startups (JOBS) Acts 2012. Thus, this study will explain the comparison between the two countries which is Indonesia and the US, regarding the regulation of the disclosure principle in ECF on the basis law, supervisory institutions, prospectus/ Bidding Documents, the minimum amount of fund. Abstrak Perkembangan teknologi sangat memberikan kemudahan bagi penggunanya tidak terkecuali dalam urusan financial technology (FinTech) yang memunculkan pula inovasi Equity Crowdfunding (ECF). ECF yaitu suatu metode pembiayaan baru mencari pendanaan untuk pengembangan Usaha Mikro Kecil Menengah (UMKM). Di beberapa negara maju seperti Amerika Serikat, ECF memiliki pengaturan prinsip keterbukaan secara sistematis. Aturan ini dimaksudkan untuk melindungi proses penyelenggaraan ECF secara legal dan profesional. Di Indonesia sendiri ECF baru saja berkembang dan sudah mengalami dua kali pergantian regulasi yaitu Peraturan Otoritas Jasa Keuangan (POJK) No. 37 2018 menjadi POJK No. 57 tahun 2020. Pengaturan prinsip keterbukaan di Indonesia masih belum cukup jelas dibandingkan dengan Amerika Serikat yang berdasarkan Title III The Jumpstart Our Business Startups (JOBS) Acts 2012. Dengan demikian, penelitian ini akan menjelaskan perbandingan kedua negara antara Indonesia dan Amerika Serikat terkait pengaturan prinsip keterbukaan pada penyelenggaraan Equity Crowdfunding terkait dasar hukum, lembaga pengawas, prospektus/Dokumen Penawaran, batas minimum jumlah penawaran penghimpunan dana, laporan keuangan penerbit, profesi penunjang, dan perlindungan investor.